2022
DOI: 10.3390/foods11071033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phenolic Extract from Red Beans (Phaseolus vulgaris L.) on T-2 Toxin-Induced Cytotoxicity in HepG2 Cells

Abstract: Red beans contain human bioactive compounds such as polyphenols. Several in vitro studies have proposed the natural compounds as an innovative strategy to modify the toxic effects produced by mycotoxins. Hence, in this work, a complete investigation of the polyphenolic fraction of red beans was performed using a Q-Orbitrap high-resolution mass spectrometry analysis. Notably, epicatechin and delphinidin were the most detected polyphenols found in red bean extracts (3.297 and 3.108 mg/Kg, respectively). Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Similarly, 15 and 30 nM T-2 significantly decreased ( p ≤ 0.05) the cell viability, while cells exposed to 7.5 nM T-2 did not show significant differences in cell viability with respect to the control. On the other hand, Martínez-Alonso et al [ 27 ] studied the viability of human hepatocarcinoma HepG2 cells exposed to T-2 (7.5, 15 and 30 nM) and observed a cytotoxic effect with 30 nM T-2. However, these authors reported that 15 nM T-2 did not affect cell viability, and 7.5 nM T-2 significantly increased cell viability due to a possible hormetic effect in HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, 15 and 30 nM T-2 significantly decreased ( p ≤ 0.05) the cell viability, while cells exposed to 7.5 nM T-2 did not show significant differences in cell viability with respect to the control. On the other hand, Martínez-Alonso et al [ 27 ] studied the viability of human hepatocarcinoma HepG2 cells exposed to T-2 (7.5, 15 and 30 nM) and observed a cytotoxic effect with 30 nM T-2. However, these authors reported that 15 nM T-2 did not affect cell viability, and 7.5 nM T-2 significantly increased cell viability due to a possible hormetic effect in HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds, besides from contributing to the smell, taste, and color of food, have a long-term intake that could play a bioactive role due to their antioxidant activity which has been related to the prevention of obesity, cardiovascular and neurodegenerative diseases, cancer, and diabetes, as well as exhibiting anti-inflammatory, antimutagenic, and antibacterial properties [11]. Madhujith et al demonstrated that beans, especially those with colored skins, possess strong antioxidant activity as measured by different model systems [12].…”
Section: Resultsmentioning
confidence: 99%
“…Delphinidin-3-glucoside and quercetin 3-O-galactoside were the most abundant polyphenols in RE and lower amounts of vanillic acid and some procyanidin dimers were also above the quantitation-allowing threshold. Interestingly, Maciel et al [ 68 ] reported that a low amount (5.39 μg/mL) of the delphinidin-3-glucoside-rich aqueous extract from Hibiscus sabdariffa acted as LC 50 (50% lethal concentration) in HepG2 cells, whereas Martìnez-Alonso et al [ 69 ] showed that the delphinidin-rich red bean extract acted by reducing ROS production. In addition, quercetin 3-O-galactoside (also known as hyperoside) was reported to arrest the HepG2 cell cycle by down-regulating the BMP-7/PI3K/AKT signaling [ 70 ].…”
Section: Discussionmentioning
confidence: 99%